Bisnis Online: Saving The Future - Mohamad Saiful Muarifin; Riris Dwi Anjani; Masduki Asbari; Adhik Ryan Niko Putratama (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to find out Jeff Budiman's perspective from the TEDxTalks youtube channel entitled "Saving The Future". in this study the researcher used a descriptive qualitative method by observing the note method because the data source was obtained by listening to oral narratives. The results of this study explain about saving the future or also called Saving The Future. This study also mentions that saving the future by setting up a business by marketing product materials through social media, because we all know that maybe Indonesia has more productive age vectors, so Indonesia will be predicted to have a golden next generation in 2045, we are predicted and many countries also claim that we will become a stopwatch, and will be recognized by the world